Robotic assisted TKA may allow for smaller polyethylene liner sizes compared to manual TKA with simultaneous removal of Hardware - Andrew D. Lachance; Alexander Edelstein; Shaya Shahsavarani; Roman Steika; Mason Stilwell; Jeffrey Lutton (Scientific Reports)
Abstract Total knee arthroplasty (TKA) with hardware around the knee is a challenge to preserve bone while boney landmarks are distorted. Robotic assisted (RA) TKA may assist in simultaneous hardware removal and TKA due to preoperative planning and retention of bone. The aim of this study is to identify if there are differences in component fixation, component constraint and functional outcomes dependent during simultaneous removal of hardware (ROH) around the knee and TKA comparing RA-TKA to manual. A retrospective chart review was performed on patients undergoing simultaneous ROH and TKA over a 10-year period at a single institution. Patients were required to have at least 6 months of follow up. Data extracted included surgical technique, demographics, range of motion (ROM) at 1 year, complications, need for augments and utilization of revision components. There were a total of 31 simultaneous ROH and TKA found in the EMR that met inclusion criteria including 23 manual and 8 RA-TKA with ROH. RA-TKA patients had significantly smaller poly sizes (p = 0.017). There was a trend for decreased need for augments (p = 0.544) and stems (p = 0.315) in the RA-TKA group although this was not statistically significant. Postoperative flexion (p = 0.973) or extension (p = 0.351) at 1 year did not vary. Notably, one patient in the manual revision group required a hinged knee, and one manual patient required an MUA. Patients undergoing ROH and RA-TKA had a statistically significant decrease in poly size with a trend of less revision component utilization. RA may allow for more boney preservation via CT guided preoperative planning and precise boney cuts.